Computer-assisted sperm analysis of freshly diluted and stored Garole ram liquid semen - JOSHI, ANIL; BAG, SADHAN; MITTAL, J P (The Indian Journal of Animal Sciences, 2012)
Computer-assisted sperm analysis technique was used in this study to objectively evaluate sperm kinematics of 32 Garole ram semen ejaculates extended @ 1: 1 with egg yolk McIllvaine glucose diluent initially, and subsequently after 24 hr of storage at refrigeration temperature. Significant (P <0.01) treatment effects were observed for motility and velocity traits. The mean motility and rapidly motile spermatozoa for freshly diluted samples were 81.8 % and 83.2 % as compared to 80.2% and 64.50%, respectively, for stored samples. The respective curvilinear, average and straight line velocities for freshly diluted and stored samples were 158.9, 130.6, 103.1 Âµm/sec and 111.3, 91.2, 75 Âµm/sec. Storage also had a significant (P <0.01) effect on mean amplitude of lateral head displacement and mean beat frequency, but there was no significant (P >0.05) effect on percent linearity and percent straightness of spermatozoa. The results indicate the usefulness of this technique for precisely evaluating the short-term preservability of Garole ram semen.